An analytical solution for the effect of initial stress, rotation, magnetic field and a periodic loading in a thermo-viscoelastic medium with a spherical cavity. Issue 1 (2nd January 2016) - Mahmoud, S. R.
ABSTRACT: In this article, an analytical solution for the effect of initial stress, the rotation, and the relaxation times in a magneto-thermo-viscoelastic homogeneous medium with a spherical cavity subjected to periodic loading is presented. The distribution of displacements, temperature, and stresses in a homogeneous medium, in the context of generalized thermo-elasticity using the Green-Lindsay (GL) theory is discussed and obtained in analytical form. The results are displayed graphically to illustrate the effect of initial stress, the rotation, relaxation times, magnetic field, and viscoelasticity. Comparisons are made with the previous work in the absence of rotation and initial stress.